2010
DOI: 10.1126/science.1197623
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Clearance of CNS β-Amyloid in Alzheimer’s Disease

Abstract: Alzheimer’s disease is associated with reduced β-amyloid clearance from the brain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
1,464
1
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,802 publications
(1,504 citation statements)
references
References 7 publications
27
1,464
1
12
Order By: Relevance
“…This result indicates that there is decreased Aß clearance, without increased Aß production, in the late stage of this AD model. This phenotype is consistent with previous human studies that Aβ clearance is impaired in both early-onset and late-onset forms of AD (Mawuenyega et al 2010;Potter et al 2013). Based on this, it seems that aged APP/PS1 mice may be available for screening potential anti-AD agents targeting at Aβ clearance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result indicates that there is decreased Aß clearance, without increased Aß production, in the late stage of this AD model. This phenotype is consistent with previous human studies that Aβ clearance is impaired in both early-onset and late-onset forms of AD (Mawuenyega et al 2010;Potter et al 2013). Based on this, it seems that aged APP/PS1 mice may be available for screening potential anti-AD agents targeting at Aβ clearance.…”
Section: Discussionsupporting
confidence: 91%
“…Excessive accumulation of neurotoxic Aβ peptides and subsequent formation of senile plaques in the brain parenchyma is the fundamental basis for the gradual, progressive development of AD pathology (Mawuenyega et al 2010;Holtzman et al 2011). An earlier study reported that diffuse amyloid plaques begin to appear in the hippocampus and cerebral cortex of APP/PS1 mice at 3 months old (Trinchese et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…APOE‐ε4 is the strongest genetic risk factor for sporadic late onset AD, and markedly accelerates A β amyloid deposition in the brain and the onset age of dementia by approximately 10 years 10, 17. Recent studies have revealed that CNS‐derived A β is cleared into the CSF28 and peripheral blood,29 and that the clearance rate is decreased in late onset AD,30 and is differently regulated by age and presence of A β amyloidosis 15, 31. Association of plasma A β levels and cortical amyloid burden is also modulated by APOE isoforms 32.…”
Section: Discussionmentioning
confidence: 99%
“…Mais il en existe d'autres, en particulier au niveau du site HincII-HBG1 et d'une séquence palindromique riche en AT du site HS4 du LCR (locus control region). Ces sites sont considérés comme en déséquilibre de liaison (LD) [3].…”
unclassified